Coeliac disease is more common in children with high socio‐economic status. (24th December 2013) - Whyte, LA; Kotecha, S; Watkins, WJ; Jenkins, HR
Abstract Aim There are a number of genetic and environmental factors that are associated with an increased risk of developing coeliac disease. Our aim was to determine whether socio‐economic deprivation increases or reduces the development of the disease. Methods A cross‐sectional study identified all children <16 years old diagnosed with coeliac disease in the same tertiary paediatric centre between January 1995 and December 2011. Data, including age at diagnosis and postcode, were collected and linked with the quintile rank of the Welsh Index of Multiple Deprivation score 2008, a measure of socio‐economic status. Results We included 232 patients and identified a graded association between the prevalence of coeliac disease and socio‐economic deprivation, which showed a higher rate in children living in more affluent areas. The largest difference was between the lowest deprivation level (rate/1000 = 1.16) and the highest deprivation level (rate/1000 = 0.49). Conclusion In our population, coeliac disease was more common in children in the higher socio‐economic groupings. The reasons for this are not clear, but perhaps both the 'hygiene hypothesis' and the health seeking behaviours of parents with high socio‐economic status are possible factors in the more frequent diagnosis of coeliac disease in this group.